The Imperative of Continuous Improvement: Enhancing Human Resources in Schools - Baharun, Hasan; Abdullah; Holifah (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2024)
The research aims to reveal the truth and conclusions about an object at the Nurul Jadid Vocational School Institution. The subject is human resources. This research found that the human resource planning carried out by the school principal and his staff was going well, so the decline in human resources each year was pretty close to a stable number. This institution has continuously improved management, learning curriculum and marketing systems. The aim is to be competitive and increase interest in the institution. Researchers used descriptive qualitative research methods. Descriptive qualitative research is a problem formulation that guides research to explore or photograph the social situation that will be researched thoroughly, broadly and in-depth. This research shows that the human resource inequality that occurs among students is caused by insufficient employee human resource quotas and inferior employee discipline, which impacts the discipline of students.